IMUNOHISTOCHEMTSTRY METHOD TO DETECT C-REACTIVE PROTEIN IN ATHEROMA PLAQUES OF SPRAGUE DAWLEY RATS FED HIGH LIPID RATION - Dhirgo Adji (Jurnal Sain Veteriner, 2007)
Since Inflammation is believed to have role in pathogenesis of cardiovasculare vents, measurement of markers of inflammation has been proposed as a method to improve the prediction of the risk of these events. C-reactive protein (CRP) a major acute phase protein, has been associated with the presence and severity of atherosclerosis, and has been found to predict acute vasculare vents in prospective studies. The aim of this study was to analyse the relationship between appearance of CRP in aorta and atheroma plaque formation in Sprague Dawley rats after 59 days induction with high fat diet. Ten male Sprague Dawley rats, 1.5 months of age were used as experimental animals. Rats were adapted in l0 single cages for 5 days and given basal diet containing normal fat and water ad libitum. After adaptation, rats were divided in to 2 groups (group 1 and group 2) of 5 each. Group I was fed basal diet containing normal fat(4.5% of fat) and group 2 was fed diet containing high fat (20% of fat). After 59 days, all rats were killed, the heart including aorta were taken out for histophatologic (HE) and immunohistochemistry analyses. The result of this study showed that all rats in Group 1 did not have atheroma plaque and CRP negative, but rats in G"cup 2, all have atheroma plaque (100%) but only 60% CRP positive. From those result it concluded that although all aortas have atheroma plaque, the CRP may not be detected in the plaque.Keywords: atheroma plaques, inflammation, C-reactive protein.